2015
DOI: 10.1111/jcpp.12378
|View full text |Cite
|
Sign up to set email alerts
|

Do infant vocabulary skills predict school‐age language and literacy outcomes?

Abstract: BackgroundStrong associations between infant vocabulary and school-age language and literacy skills would have important practical and theoretical implications: Preschool assessment of vocabulary skills could be used to identify children at risk of reading and language difficulties, and vocabulary could be viewed as a cognitive foundation for reading. However, evidence to date suggests predictive ability from infant vocabulary to later language and literacy is low. This study provides an investigation into, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
174
2
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(225 citation statements)
references
References 35 publications
(57 reference statements)
21
174
2
12
Order By: Relevance
“…consistent with behavioral evidence for the influence of parent-child reading exclusively on "outside-in" oral language skills (understanding outside of the word itself) described by Whitehurst et al 1,5 Vocabulary is among the most important of these skills, 70 shown to be influenced by home reading environment 17 and recently found to be positively associated with left angular gyrus activation during our story listening task in young children. 49 Thus, PTO activation may offer potential as a biomarker of oral language ability (the outside-in domain of emergent literacy), although further studies are needed to clarify how the PTO is integrated into the reading network.…”
Section: Figuresupporting
confidence: 86%
“…consistent with behavioral evidence for the influence of parent-child reading exclusively on "outside-in" oral language skills (understanding outside of the word itself) described by Whitehurst et al 1,5 Vocabulary is among the most important of these skills, 70 shown to be influenced by home reading environment 17 and recently found to be positively associated with left angular gyrus activation during our story listening task in young children. 49 Thus, PTO activation may offer potential as a biomarker of oral language ability (the outside-in domain of emergent literacy), although further studies are needed to clarify how the PTO is integrated into the reading network.…”
Section: Figuresupporting
confidence: 86%
“…Some experts have suggested that five years of age represents a time-point in which children's vocabulary skills become stable, following a period of great instability during the toddler and preschool years (Duff, Reen, Plunkett, & Nation, 2015). Duff and colleagues' examination of growth in vocabulary skills from toddlerhood (18 to 24 months) to around eight years of age showed that early vocabulary skills explained about 16% of the variance in vocabulary at eight years, whereas our study showed that vocabulary at about five years explained 50% of the variance in vocabulary at grade three.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies examining trajectories have featured more frequent observations of children (Farkas & Beron, 2004;Rowe et al, 2012), and it may be that more precise assessment of linguistic change is necessary to represent trajectories during early and middle childhood. This is an important methodological consideration for research on children's language development, given that even at very young ages, children's language skills show significant change in even relatively small increments of time (Duff et al, 2015). Finally, we did not represent the nested data-structure of this study into our modeling, although children were nested in classrooms at the initial observation and then longitudinally.…”
Section: Discussionmentioning
confidence: 99%
“…In this sample, 17% of high risk infants went on to have ASD themselves, and an additional 11% demonstrated signs of early language delay but not ASD. Recent community sample studies have suggested that early language skills are correlated with school-age vocabulary and literacy; however, the relationship is insufficiently strong to predict individual outcomes from infant data (55). School-age children with a family history of ASD have higher than expected rates of impairment, including difficulties in speech and language (56), thus early language delays in high-risk infants may herald these school-age difficulties, but this link remains to be determined.…”
Section: Discussionmentioning
confidence: 99%